NIC6-TT Vaccine Reduces Nicotine-Seeking Behavior and Expression of Nicotine-Induced Locomotor Sensitization in Rats - Susana Barbosa Méndez; Alberto Salazar-Juárez (Brain Sciences)
Introduction: Various models of nicotine vaccines have been evaluated. In humans, antibody levels are low and variable. In this sense, it is necessary to improve or optimize the nicotine vaccines already evaluated. We reported the efficacy of the M6-TT vaccine. Recently, we reported the efficacy of the COC-TT vaccine, which was developed from the M6-TT vaccine. Both vaccines generate high titers of antibodies and attenuate heroin- or cocaine-induced behavioral effects in rodents. Aims and Methods: The objective of this study was to determine whether the antibodies generated by a tetanus toxoid-conjugated nicotine vaccine (NIC6-TT) can produce anti-nicotine antibodies and decrease the nicotine-induced reinforcing and psychomotor effects. Male Wistar rats were immunized with the NIC6-TT. A solid-phase antibody-capture ELISA was used to monitor antibody titer responses after each booster dose in vaccinated animals. The study used nicotine self-administration and nicotine locomotor sensitization testing to evaluate the nicotine-reinforcing and psychomotor effects. Results: The NIC6-TT vaccine could generate high and sustained levels of anti-nicotine antibodies. The antibodies reduced the nicotine self-administration and expression of nicotine locomotor sensitization. Conclusions: These findings suggest that the NIC6-TT vaccine generates a robust immunogenic response capable of reducing the reinforcing and psychomotor effects of nicotine, which supports its possible future use in clinical trials for the treatment of smokers. Implications: Smoking is the second most used psychoactive substance in the world, which is associated with millions of preventable deaths. An effective treatment is required. Nicotine vaccines must generate high levels of anti-nicotine antibodies, but above all, the decay curve of the antibodies must be very slow, so that they can provide long-term protection and support long-term smoking abstinence. The NIC6-TT vaccine meets these properties.